CHANGING THE ENVIRONMENTAL PARADIGM THROUGH 3R (Reuse, Reduce, Recycle) EDUCATION: Student Devotion to Plastic Waste Management and Sustainable Creativity with Economical Value - Supardi Supardi (Jurnal PKM Manajemen Bisnis, 2023)
The environment is home to all forms of life, especially humans, and protecting it is an absolute obligation. Environmental quality greatly affects human life. Even though there are many ways to protect the environment, careless waste handling is still a troubling problem. Piles of garbage on the streets and especially plastic waste, which is difficult to decompose, are increasingly widespread and have an increasingly serious impact. To respond to this, we as academic members feel the need to contribute in the form of Student Community Service, which we do at the Al Kamilah Foundation, Jl. Raya No. 3, Serua, Bojongsari District, Depok City, West Java. Our main goal is to increase awareness of the dangers of plastic waste and teach them how to process it into valuable and economically valuable goods. We apply the 3R (Reuse, Reduce, Recycle) training method with a focus on making piggy banks from plastic bottles. The results of this activity indicated the enthusiasm of the participants in learning and being creative with plastic waste. The resulting creations are not only useful as a place to store pocket money, but also have the potential to be used as business products. Through this activity, we hope to be able to provide valuable learning to the participants and open the door for ongoing training to improve their ability to manage plastic waste in an innovative and sustainable way.